Late results of Maze and pulmonary vein isolation procedures for atrial fibrillation - YAMAUCHI, Masanobu; KANETSUKI, Kazuma; KAMIHIRA, Satoshi; HANADA, Tomoki (Medical Journal of Shimane Prefectural Central Hospital, 2021)
The effectiveness of maintaining rhythm by Maze and pulmonary vein isolation（PVI） procedures, which are surgical operations for atrial ﬁbrillation（AF）, is clear, and in addition, it has been shown to improve survival rate and prevent the onset of cerebral infarction. This time, we examined the late results after maze and PVI procedures at our hospital. The subjects were 77 cases from 1999 to June 2019, with 54 cases of chronic AF, 23 cases of paroxysmal atrial ﬁbrillation, average age of 70 years, and 62％（48 cases） were male. The surgical procedure was 50 cases of biatrial maze, 19 cases of PVI, 7 cases of left atrial maze, and one case of right atrial maze. With 3 hospital deaths and 18 remote deaths, the survival rate was 96％ for 1 year, 88％ for 5 years, 71％ for 10 years, and 56％ for 15 years, which is the same as the life expectancy of 70 years old. The AF free rate at discharge was 85％, and the late AF free rate at an average observation period of 5.9 years was 63％. The AF free rate by Kaplan-Meier method decreased over time to 97％ for 1 year, 82％ for 5 years, 57％ for 10 years, and 37％ for 15 years. We compared 47 cases of remote sinus rhythm （SR） with 28 cases of AF. Univariate analysis revealed signiﬁcant diﬀerences in postoperative left atrial（LA）diameter, SR at discharge, and late mortality. In multivariate analysis, the factors of remote SR were Maze procedure, postoperative LA diameter, and discharge at SR. In the ROC curve, the postoperative LA diameter of 47.5 mm was the cut-oﬀ value for maintaining SR in the remote period, and 77％ of the postoperative LA diameter of less than 47.5 mm was SR, but that of 47.5 mm or more was 44％. Anticoagulant therapy was continued in 73％ of patients after surgery, and cerebral infarction occurred in 5.5％ of 4 patients, all of whom were on anticoagulant therapy. Left atrial appendage occlusion was performed in 18 of the 20 patients who discontinued anticoagulant therapy, and no cerebral infarction occurred. Catheter ablation was performed in 4 postoperative cases, and all cases recovered to SR and were eﬀective.